2010
DOI: 10.1007/s13258-010-0066-x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of the silkworm strains (Bombyx mori): high variability and potential markers for strain identification

Abstract: The silkworm (Bombyx mori) is of great economic value from an industrial perspective. Casual discrimination and accumulation of genetic information from a diverse variety of silkworms are essential for practical utilization and long-term conservation. In this study, a total of 54 silkworm strains preserved in Korea were typed for nine polymorphic microsatellite loci. We determined per-locus numbers of alleles ranging from 3 to 17 with an average value of 7.5, per-locus observed heterozygosity ranging from 0.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Due by these merits microsatellite DNA has been used in many organisms for a diverse purpose (Edwards et al, 1991;Morgante and Olivieri, 1993;Dallas et al, 1995;Viard et al, 1996;Mariat et al, 1996;Pope et al, 1996;Romero et al, 2003). In the silkworm, abundant microsatellite primers have been published by several authors (e.g., Dharma Prasad et al, 2005), but only some of the Chinese strains kept in Korea were genotyped using microsatellite DNA (Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due by these merits microsatellite DNA has been used in many organisms for a diverse purpose (Edwards et al, 1991;Morgante and Olivieri, 1993;Dallas et al, 1995;Viard et al, 1996;Mariat et al, 1996;Pope et al, 1996;Romero et al, 2003). In the silkworm, abundant microsatellite primers have been published by several authors (e.g., Dharma Prasad et al, 2005), but only some of the Chinese strains kept in Korea were genotyped using microsatellite DNA (Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The previous analysis of strains from China reported PIC values ranging from 0.34 to 0.82, with an average of 0.54 per locus (Kim et al, 2012). Furthermore, Kim et al (2010) reported that 54 silkworm strains originating from several countries exhibited a mean PIC value of 0.47 over all loci (nine loci, including the eight loci used in this study). The PIC values at each locus ranged from 0.06 to 0.86, which is slightly higher than the values we calculated for the strains from Japan.…”
Section: Analysis Of Variation and Phylogenetic Tree Constructionmentioning
confidence: 52%
“…Previous studies of silkworm strains originating from China also support this notion (Kim et al, 2010(Kim et al, , 2012.…”
Section: Relationships Among Silkworm Strainsmentioning
confidence: 62%
See 2 more Smart Citations